The Effects of Parental Involvement on Storytelling with a Package of Role-Play Activities on the Growth Mindset of Early Childhood - Whangmooklang, Narudee; Samahito, Chalatip (An Online Journal of Education, 2022)
The purpose of this research was to study the effect of parental involvement on storytelling with a package of role-play activities on the growth mindset of early childhood. The target groups included 6 young children, 5-6 years old and 6 parents of the target group. In addition, the parents had to have knowledge and the ability to use technology to communicate. The research instruments consisted of: 1) plans on using storytelling activity provision with role plays and parental involvement on the growth mindset of early childhood; 2) an assessment form on the growth mindset of early childhood; 3) a behavioral observation form for parents on the growth mindset of early childhood; 4) a satisfaction questionnaire and suggestions from parents; 5) an assessment form for parents on knowledge, understanding, and attitudes on the growth mindset; and 6) an unstructured parental interview form. The obtained data were analyzed by mean, standard deviation, and content analysis. The results showed that 1) children had a higher growth mindset after the experiment than before; 2) children’s growth mindset on the aspect of the success of others increased the most; 3) the story in the activity package that children paid the most attention was Khun Rabbit's Tailor Shop; 4) parents had average scores for knowledge, understanding, and attitudes towards a growth mindset were higher than before the experiment. 5) parents were satisfied with the activity packages at the highest level of 80.95% and the lowest level at 19.05%, parents see their children have more open-minded and more efforts.